(untitled) (Experimental biology, 2015)
The nutritional value of camel meat is similar to other red meats but camel meat, especially from young animals,can be considered as a healthy option due to the low fat and cholesterol contents of the meat. In appearance and colour,texture and palatability, camel meat is very similar to beef. Camel is useful for healthy skin and mucous membranes,nervous and digestive systems. Trace elements included in the meat, to regulate blood sugar. Camel meat contains antioxidants. Quality parameters of individual muscles can be used to improve marketing of camel meat, and would provide more information about meat quality characteristics of camel meat.